Going public - going private: The case of VC-backed firms - Andrej Gill; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
We investigate the decisions of listed firms to go private once again. We start by revealing that while a significant number of firms which go public is VC-backed, an overproportional share of these VC-backed firms go private later on (they stay on the exchange for an average of 8.5 years). We interpret this very robust pattern such that IPOs of VC-backed firms are to a large extent a temporary rather than a permanent feature of the corporate governance of these firms. We investigate various potential hypotheses why VCs actually seem to be able to bring marginal firms to the exchange by relating the going-private decisions to various characteristics of the IPO market as well as to VC characteristics. We find strong support for the certification ability of VCs: more experienced and reputable VCs are more able to bring marginal firms to public exchanges via an IPOs. These marginal firms backed-by more reputable and experienced VCs are more likely to go private later on. Hence, our analysis suggests that IPOs backed by experienced VCs are most likely to be a temporary rather than the final stage in the life of the portfolio firm. We find no support that reputable VCs underprice their IPO-exits more implying that they have no need to leave more money on the table to take the marginal firms public.
urn:nbn:de:hebis:30:3-240579
Keywords: G24; G34; D80; 330; Going-private decisions; VC-backed IPOs; corporate governance; Wertpapieremission; Going Private; Unternehmensentwicklung; Risikokapital; Schätzung; USA